(untitled) (Palestine Technical College Journal for Research and Studies, 2019)
The study aimed to identify the reality of articulation, speech and language disorders in children at pre-school stage in Gaza Governorate. The study was applied in Gaza governorate (West Gaza Directorate, East Gaza Directorate) on a sample of (5715) children, The interview was used to examine children and identify their disorders through an individual screening card prepared for this purpose, and the descriptive screening method was used as an appropriate method to collect the data of this phenomenon, which was processed statistically through some statistical methods such as repetitions and percentages of the answers to the questions of the study and the most important results are as follows: 1. There are Articulation disorders in children at pre-school stage c in Gaza Governorate by 15.905%. 2. There are speech disorders in children at preschool stage in Gaza Governorate by 2.047%. 3. There are language disorders in children at pre-school stage in Gaza Governorate are 4.64%.